EXPERIENCES IN USING INNOVATIVE BANKING SERVICES IN DEVELOPED COUNTRIES (Marketing Journal, 2025)
The article analyzes innovative banking services provided by commercial banks in developed countries. In particular, it examines private banking services targeting high-net-worth individuals, digital technology -based products, and competitive advantages in various banking service segments. The analysis reveals that service quality and diversity, personalized approaches, and digital transformation represent the main directions of international experience. The article concludes with recommendations for the ba nking system of Uzbekistan.
Keywords: innovative banking services; commercial bank; digital technologies; high-net-worth individuals; transformation; private banking. 597